2020
DOI: 10.1101/2020.05.20.106039
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissecting HSV-1-induced host shut-off at RNA level

Abstract: 26Herpes simplex virus 1 (HSV-1) installs a profound host shut-off during lytic infection. 27 The virion host shut-off (vhs) protein plays a key role in this process by efficiently 28 cleaving both host and viral mRNAs in a translation-initiation-dependent manner. 29 Furthermore, the onset of viral DNA replication is accompanied by a rapid decline in 30 transcriptional activity of the host genome. Both mechanisms have tremendous impact 31 on the RNA expression profile of the infected cells. To dissect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Notably, we previously showed that transcriptional activity on host genes drops substantially in the first 4 h of infection to only 40% of transcription in uninfected cells, which was further halved until 8 h p.i. (19). Thus, the onset of the extension of accessible chromatin regions at promoters into downstream (for pattern (i)) and upstream (for pattern (ii)) regions follows the onset of the drop in host transcription during infection.…”
Section: Changes In Chromatin Accessibility Manifest Between 4 and 6 ...mentioning
confidence: 97%
See 4 more Smart Citations
“…Notably, we previously showed that transcriptional activity on host genes drops substantially in the first 4 h of infection to only 40% of transcription in uninfected cells, which was further halved until 8 h p.i. (19). Thus, the onset of the extension of accessible chromatin regions at promoters into downstream (for pattern (i)) and upstream (for pattern (ii)) regions follows the onset of the drop in host transcription during infection.…”
Section: Changes In Chromatin Accessibility Manifest Between 4 and 6 ...mentioning
confidence: 97%
“…To correlate transcriptional activity of genes to the observed patterns in chromatin accessibility changes, we analyzed RNA-seq data of chromatin-associated RNA for mock and 8 h p.i. WT HSV-1 infection from our recent study (20). Chromatin-associated RNA depicts ongoing nascent transcription on the chromatin.…”
Section: -17)mentioning
confidence: 99%
See 3 more Smart Citations